Role of Hydrogen Peroxide (H2O2) and Trichoderma koningii in Reducing Root Rot Disease of Tomato Causing by Fusarium solani - Madhi, Qusai H.; Yehya A. Salih; Ghassan M. Daghir (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
Two isolates of the pathogenic fungus Fusarium solani the causative of tomato root rot disease named Fs1 and Fs2 were isolated from tomato plants infected with root rot disease. Results showed that both examined isolates had significant effects on the percentage of seed germination of tomato and damping-off disease. Thus, isolate Fs1 was more effective than isolate Fs2, as it recorded a percentage of germination and damping-off 56.6 and 71.6% respectively, compared to the control treatment, which recorded 100 and 0% respectively. It was found that the use of hydrogen peroxide (H2O2) at concentrations of 50, 100 and 200 ppm had a significant effect on the fungal radial growth, dry weight (DW) and sporulation of F. solani. Antifungal activity of H2O2 appeared even at the lowest concentration (50 ppm), which inhibited radial growth to 49.33%, and decreased the dry weight to 498 mg, and the sporulation to 3.75×106 spores. Additionally, the results indicated significant inhibitory effects of hydrogen peroxide (H2O2) and the bioagent Trichoderma koningii on F. solani growth. It was noticed that H2O2 has compatible effects with T. koningii, where the antagonistic ability of T. koningii against F. solani increased when the concentration of H2O2 had increased. The results revealed that the treatment F. solani + H2O2 (200 ppm) + T. koningii significantly reduced the percentage of damping-off and plant survival to 9.40 and 5.39% respectively, in comparison with the control treatment and F. solani alone treatment, which reached 20.22, 14.48, 34.32 and 67.41% respectively.